Catcalling victims’ long-term psychological impacts: A qualitative study - Avezahra, Mutia Husna; Kamila, Aida Annisa Nur; Maulana, Nandyang Akhsanul; Kravvariti, Vasiliki; Sa’id, Mochammad; Noorrizki, Rakhmaditya Dewi (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Catcalling incidents are a form of street harassment that occurs in public spaces, conducted by strangers through verbal expressions and behavioral intentions with sexual nuances. This research investigates the psychological dynamics of catcalling events as women perceive them. A qualitative method involves a phenomenological approach and recruiting four participants using purposive sampling. Data were collected from semi-structured interviews, with thematic data analysis using the qualitative data management software NVivo 12. The trustworthiness strategy of the research includes reflexive journaling during the thematic analysis process and a participant-checking procedure. The findings show that catcalling incidents contribute to negative feelings and destructive self-perceptions. In the short term, the psychological impacts of catcalling include fear and worry, discomfort, anxiety, and increased alertness when facing unsafe situations, while the long-term impacts include feelings of guilt, criticism of one’s body shape and appearance, and feeling ashamed of one’s identity as a woman. The research argues that negative body images resulting from catcalling incidents contribute to the risk of low self-esteem.